DEVELOPMENT OF BATUTULIS PLAN AS A BOGOR CITY TOURISM AREA - Saragi, Charles Parnauli; Hermawan, Yanto; Nurachmad, Edi; Salsabila, Siti Yasmin; Herawati, Fitria; Utami, Nisa Rahmaniyah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Tourists take historical tours to experience firsthand the places and activities that depict the history of the people in the past. The trend of tourism activities that are in great demand by tourists encourages the provision of tourism activities that involve story telling and are thick with adventure values. To find out the extent to which the potential in the Batutulis and Lawanggintung areas of South Bogor District can be developed, it is necessary to prepare a detailed plan as a strategy and direction for the development of the Batutulis and Lawanggintung areas of South Bogor District as a City Tourism Strategic Area (KSPK). The purpose of the researcher is to identify the potential for the development of the Batutulis City Tourism Strategic Area (KSPK), South Bogor District. The data analysis methods used are quantitative and qualitative. Based on the evaluation obtained during this Community Service activity, it can be concluded that the Batu Tulis City Strategic Area Plan (KSPK) is an effort to support tourism activities which are expected to increase economic activities and community welfare through the introduction of historical relics.